UTILIZATION OF DIGITAL TECHNOLOGY, LOCAL WISDOM, ECONOMIC LITERACY AND ITS IMPACT ON STUDENT BUSINESS PERFORMANCE IN THE DIGITAL - Allen A. CH Manongko; Vinda Afnita; Lidia Aprileny Hutahaean (International Journal of Cultural and Social Science, 2025)
This study aims to analyze the influence of Digital Technology Utilization, Local Wisdom Integration, and Economic Literacy on Student Business Performance (UMKM). The background of the study is rooted in the importance of strengthening student entrepreneurship in the digital era and local-based context, especially in facing market competition and the need to adapt to technological advances and cultural values. The research employed a quantitative approach with an associative design. The sample consisted of 40 student entrepreneurs from the Economic Education Department at FEB UNIMA, selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed using simple and multiple linear regression. The results indicate that each independent variable (X1, X2, and X3) has a positive and significant effect on student business performance when tested separately. However, in the multiple regression model, although the overall model is statistically significant, the individual effects of each variable are not significant. The coefficient of determination (R²) of 0.297 indicates that the three variables combined explain 29.7% of the variance in student business performance. This study recommends a synergistic strategy combining digitalization, local culture preservation, and improved economic literacy to support the sustainable development of student-run UMKM.